The resurrection of Charybdis (Gonioinfradens) giardi (Nobili, 1905), newly recorded from the SE Mediterranean Sea - Galil, Bella S.; Douek, Jacob; Gevili, Roy; Goren, Menachem; Yudkovsky, Yana; Paz, Guy; Rinekvich, Baruch (Zootaxa, 2018)
A single adult specimen of Gonioinfradens giardi, a portunid crab known from the Red Sea, Gulf of Oman and Arabian Gulf, was recently collected off the southern Israeli coast, in the southeastern Mediterranean Sea. Morphological characters, as well as molecular analyses based on the mitochondrial barcoding gene cytochrome oxidase sub unit I (COI), support its distinction from the widely distributed G. paucidentata. Therefore, G. giardi is reinstated as a valid species, and withdrawn from its synonymy with G. paucidentata. Previous Mediterranean records of the latter species are misidentifications and should be referred to G. giardi. The species is described, illustrated, and differentiated from its cogener.